2009
DOI: 10.3390/s90402682
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Thin Films for Gas Sensors Prepared by Matrix Assisted Pulsed Laser Evaporation

Abstract: The matrix assisted pulsed laser evaporation (MAPLE) technique has been used for the deposition of metal dioxide (TiO2, SnO2) nanoparticle thin films for gas sensor applications. For this purpose, colloidal metal dioxide nanoparticles were diluted in volatile solvents, the solution was frozen at the liquid nitrogen temperature and irradiated with a pulsed excimer laser. The dioxide nanoparticles were deposited on Si and Al2O3 substrates. A rather uniform distribution of TiO2 nanoparticles with an average size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…Porous nanostructured layers have been studied especially in the context of gas sensing materials (Caricato et al, 2009;Nam et al, 2006). PLD offers many advantages compared to other deposition methods, for example easily controllable film composition by deposition parameters, and a good repetition of stoichiometry of the target material in the films deposited on the substrate.…”
mentioning
confidence: 99%
“…Porous nanostructured layers have been studied especially in the context of gas sensing materials (Caricato et al, 2009;Nam et al, 2006). PLD offers many advantages compared to other deposition methods, for example easily controllable film composition by deposition parameters, and a good repetition of stoichiometry of the target material in the films deposited on the substrate.…”
mentioning
confidence: 99%
“…Die mit den unterschiedlichen Methoden erhaltenen Materialien und Filme werden diskutiert und hinsichtlich ihrer Strukturparameter und Leistung klassifiziert. Über einige der Trockenmethoden wie Matrix-unterstützte Verdampfung mit gepulstem Laser (Matrix Assisted Pulsed Laser Evaporation), [63] (gepulste) Laserablation, [58] Atomlagenabscheidung, [64] Flammensynthese, [65] Laserstrahlverdampfen und reaktive Molekularstrahlepitaxie gibt es bereits eigene Aufsätze. [66] Hier werden wir uns auf die technischen Aspekte derjenigen Herstellungsmethoden konzentrieren, die für das funktionelle Design von Sensorfilmen geeignet sind.…”
Section: Introductionunclassified
“…Wu et al [57] deposited carbon nanotube film by MAPLE method. And after that success, TiO 2 and SnO 2 nanoparticles were deposited by the researchers [58]. After characterization, the researchers found that the nanoparticles maintain same crystal structure and size.…”
Section: Nanoparticlesmentioning
confidence: 99%